Estimation Age of Bloodstain Using Smartphone Application on Colorimetric Analysis - Reinhard Saliama (Universitas Airlangga, 2023)
Advances in technology should be able to help the work of forensic experts, especially in solving criminal crime cases. Estimated age of bloodstains is an important factor in forensic analysis. This study aims to identify the age of bloodstains using the colorimetric method and observe changes in the color of bloodstains on the surface of the material based on the results of photos using a smartphone camera. This study is an experimental study with a control time series design, where bloodstain samples are observed in a certain period longitudinally. Bloodstains were dripped on five different material surfaces, namely ceramics, glass, cardboard, paper, and newspapers, then observations and taking photos of bloodstains for 72 hours. Estimation of the age of bloodstains using artificial neural tissue by the backpropagation method. The results showed that the artificial neural network that was built was able to predict the age of bloodstains based on time classification. In addition, there is a significant influence of the color of bloodstains on the five surfaces of ceramic, glass, cardboard, paper and newspaper materials, namely. 63.7%; 84.3%; 84.6%; 68.2% and 86.6%.